O uso da farinha da casca de banana in natura e quimicamente modificada com tiosemicarbazida na adsorção de arsênio, antimônio e selênio - Paniagua, Cleiseano Emanuel da Silva (2015)
This paper describes the use of banana peel flour in natura and chemically modified with thiosemicarbazide in the adsorption of arsenic, antimony and selenium.The adsorbent material: as natural banana flour (FBN) and banana flour impregnated with thiosemicarbazide (FBM) was characterized using the following techniques: (1) Middle Infrared Spectroscopy Fourier Transform (FT-MIR) (2) Scanning Electron Microscopy (SEM), (3) ray Diffraction (XRD), (4) Thermogravimetric Analysis (TGA), (5) Elemental Analysis (CNHS) and (6) Zero Charge Point (PCZ). It was later made the optimization of the variables in the HG-AAS: sample concentration of HCl and NaBH4; sample flow and NaBH4 for metals arsenic, antimony and selenium, obtaining the following results: (I) antimony: concentration of Sb (III) at 20 μg L-1; HCl concentration of 5.0 mol L-1; NaBH4 concentration of 0.4% (w / v); Flow concentration of Sb (III) and 10 ml min -1 flow of NaBH4 concentration of 1.5 ml min -1 (II) Arsenic: Concentration of As (III) 20 μg L-1; concentration of HCl of 7.0 mol L-1; NaBH4 concentration of 0.6% (w / v); Flow concentration of As (III) 10.0 ml min -1 flow rate and NaBH4 concentration of 2.0 ml min -1. (III) selenium: concentration of Se (IV) at 20 μg L-1; HCl concentration of 10.0 mol L-1; NaBH4 concentration of 0.4% (w / v); flow rate of concentration of Se(IV) of 10.0 ml min -1 flow of NaBH4 concentration of 1.5 mL min -1, and the HCl flow was set at 2.5 mL min -1 for all metals. After adsorption was performed assays studying the pH, contact time, and the adsorbent mass as variables in the adsorption process, obtaining the following results: (I) arsenic pH = 4 in FBN (25% ) in FBM (60%); the mass of adsorbent in FBM 0.250g (90%) and a residence time of 60 min in FBM (92%); (II) antimony pH = 4 in FBN (> 20%) and FBM (60%); the mass of adsorbent in FBM 0.250 g (85%) and contact time of 60 minutes FBM (85%); (Iii) selenium pH = 4 in FBN (25%) and FBM (60%); the mass of adsorbent in FBM (80%) and a residence time of 90 minutes FBM (80%). Adsorption isotherms were described using the model of Langmuir and Freundlich, obtaining very next. Finally, the method was applied in synthetic samples of sea water spiked with As (III), Sb (III) and Se (IV). Results of removal for As (73.57%), Sb (65.89%) and Se (59.73%) demonstrates that the proposed method is applicable to samples of environmental interest.